Non-functional paraganglioma of the urinary bladder: a case report - Xu, Dan-Feng (BioMed Central, 2010)
INTRODUCTION: Paragangliomas that originate from the urinary bladder are extremely rare. In most series, bladder paragangliomas often cause micturitional attacks. Treatment modalities include transurethral resection and cystectomy (partial or total). Prognosis of bladder paraganglioma is similar to that of adrenal pheochromocytoma. CASE PRESENTATION: A 55-year-old Chinese woman presenting with the sole complaint of lower abdominal pain for one month was admitted to our hospital. Ultrasound and computed tomography revealed a mass on the dome of the bladder measuring 4.0 × 3.0 cm. The tumor was completed removed by laparoscopic partial cystectomy. Histological examination of the tumor indicated paraganglioma of the urinary bladder. The clinical features, diagnosis, management and pathological findings of paraganglioma of the urinary bladder are discussed. CONCLUSIONS: Bladder paraganglioma should be considered as a differential diagnosis to neoplasm in the urinary bladder, although there is no characteristic symptom. Laparoscopic partial cystectomy may be the first choice in treating paraganglioma of the urinary bladder, offering several advantages such as less invasion, rapid recovery and early discharge from the hospital.